PERANCANGAN VIDEO PROFIL NANAS AGENCY MENGGUNAKAN TEKNIK MOTION GRAPHIC SEBAGAI MEDIA PROMOSI - Adiptia, Lorensio Deka; Kusumandyoko, Tri Cahyo (BARIK, 2023)
The advancement of digital technology in recent years has brought significant changes in the way people interact with content, particularly video content. Videos have proven to be advantageous in capturing attention and enhancing understanding, making them effective tools for communication and promotion. This thesis aims to design a company profile video for Nanas Agency as a communication tool and promotional medium. The research methodology employed is Design Thinking proposed by Kelley & Brown (2018), comprising the stages of Empathize, Define, Ideate, Prototype, and Test. The video profile is created using Motion Graphic techniques with a Corporate Memphis style theme. The video production process involves thumbnail, tight issue, and final design stages, resulting in a 3 minutes 46 seconds company profile video. The feasibility test reveals a high percentage, indicating that the Motion Graphic company profile video for Nanas Agency successfully conveys the message clearly and receives positive responses from the audience. The findings of this research contribute to the understanding of how Motion Graphic videos can be utilized as effective communication tools for company promotion in the digital era.Keywords: Video Profile, Motion Graphic, Promotion.